oHealth: A self-care android application for senior citizens with hypertension - Phukkhapan Ghoshachandra (2018)
© 2017 IEEE. Currently, most of senior citizens in the world have hypertension and the number of patients tend to increase every year because senior citizens do not know how to take care of themselves. They do not know how often and when the best time to measure blood pressure. In order to guide senior citizens with hypertension to take care of themselves, oHealth, a self-care android application, was proposed. By using oHealth application connected with blood pressure device, senior citizens can measure and monitor their blood pressure daily at home anytime. In each day, they can also record about medicines and food intake and exercise for treatment. All records are kept in azure SQL database. Moreover, this application also provides user interface design that is suit for senior citizens. oHealth application has six main functions which are manage profile, measure blood pressure, provide knowledge, record treatment, provide reminders, and perform data analysis by using multiclass logistic regression method in azure machine learning. The ultimate goal of oHealth application is to assist senior citizens to prevent, evaluate, and treat hypertension, and to help them control medicine, food, and exercise to treat hypertension in an appropriate way.